One-pot synthesis of S-scheme MoS2/g-C3N4 heterojunction as effective visible light photocatalyst - Ha Tran Huu (Nature Portfolio, 2021)
Abstract Despite pioneering as the holy grail in photocatalysts, abundant reports have demonstrated that g-C3N4 performs poor photocatalytic activity due to its high recombination rate of photo-induced charge carriers. Many efforts have been conducted to overcome this limitation in which the semiconductor–semiconductor coupling strategies toward heterojunction formation were considered as the easiest but the most effective method. Herein, a one-pot solid-state reaction of thiourea and sodium molybdate as precursors at different temperatures under N2 gas was applied for preparing composites of MoS2/g-C3N4. The physicochemical characterization of the final products determines the variation in contents of components (MoS2 and g-C3N4) via the increase of synthesis temperature. The enhanced photocatalytic activity of the MoS2/g-C3N4 composites was evaluated by the degradation of Rhodamine B in an aqueous solution under visible light. Therein, composites synthesized at 500 °C showed the best photocatalytic performance with a degradation efficiency of 90%, much higher than that of single g-C3N4. The significant improvement in photocatalytic performance is attributed to the enhancement in light-harvesting and extension in photo-induced charge carriers’ lifetime of composites which are originated from the synergic effect between the components. Besides, the photocatalytic mechanism is demonstrated to well-fit into the S-scheme pathway with apparent evidences.